2015
DOI: 10.1177/0956462415570159
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of and intentions to adopt HIV pre-exposure prophylaxis among black men who have sex with men in Los Angeles

Abstract: This study assessed perceptions of Pre-Exposure Prophylaxis (PrEP) and their association with PrEP adoption intention among a convenience sample of 224 low socioeconomic status black men who have sex with men (BMSM) residing in Los Angeles. Participants received educational information about PrEP and completed an in-person interview. More than half (60%) of participants indicated a high intention to adopt PrEP. Younger BMSM (18-29 years) were twice as likely to report a high intention to adopt PrEP compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 39 publications
1
37
0
7
Order By: Relevance
“…Finally, findings also suggest that there are likely complex psychological and social changes that occur in the context of PrEP use that can help us to elucidate a more comprehensive view of risks to adherence and for potential non-HIV STIs, and at the same time provide insights into potential avenues for ongoing risk-reduction interventions for substance-using MSM. For example, many of the participants in the current study reported decreased levels of fear and anxiety around having sex in general and stated that they felt that PrEP provided an “added layer of protection” against HIV (Brooks, Landovitz, Regan, Lee, & Allen, 2015; Perez-Figueroa, Kapadia, Barton, Eddy, & Halkitis, 2015). While this finding might suggest some men are more likely to engage in more frequent condomless anal sex, participants often reported feeling more empowered taking PrEP and felt as though they were proactively taking care of their sexual health—i.e., getting regular HIV and STI testing, rapidly treating any STIs, and notifying partners of possible STI exposure.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, findings also suggest that there are likely complex psychological and social changes that occur in the context of PrEP use that can help us to elucidate a more comprehensive view of risks to adherence and for potential non-HIV STIs, and at the same time provide insights into potential avenues for ongoing risk-reduction interventions for substance-using MSM. For example, many of the participants in the current study reported decreased levels of fear and anxiety around having sex in general and stated that they felt that PrEP provided an “added layer of protection” against HIV (Brooks, Landovitz, Regan, Lee, & Allen, 2015; Perez-Figueroa, Kapadia, Barton, Eddy, & Halkitis, 2015). While this finding might suggest some men are more likely to engage in more frequent condomless anal sex, participants often reported feeling more empowered taking PrEP and felt as though they were proactively taking care of their sexual health—i.e., getting regular HIV and STI testing, rapidly treating any STIs, and notifying partners of possible STI exposure.…”
Section: Discussionmentioning
confidence: 85%
“…This analysis moves beyond barriers identified in prior research, such as cost, side effects, accessibility, attitudes towards PrEP, and concern with drug resistance, 1621 to focus on belief in HIV/AIDS conspiracies, a phenomenon prevalent among African Americans, with potential implications for scaling up PrEP with black MSM.…”
Section: Introductionmentioning
confidence: 99%
“…8 Current estimates indicate that 24.9% of black MSM who are seronegative at age 18 will become HIV-positive by age 25; 3 however, the introduction of PrEP into this community may make a critical difference, especially since younger black MSM may be more likely to accept PrEP than older black MSM. 9 Black MSM continue to be highly impacted in Los Angeles County (LAC) as well, where the HIV incidence rate for blacks was three-times the rate for whites and Latinos. 10 On July 16, 2012, the US Food and Drug Administration approved Truvada in combination with condom use and other safer sex practices to reduce the risk of sexually acquired HIV-infection as a form of PrEP.…”
mentioning
confidence: 99%